ROLE OF MULTIPLEX CYTOKINE ANALYSIS IN THE EVALUATION OF THE EFFICACY OF RITUXIMAB DURING TREATMENT FOR RHEUMATOID ARTHRITIS - A. A. Novikov; E. N. Aleksandrova; T. V. Popkova; O. G. Lineva; A. S. Avdeyeva; D. S. Novikova; G. Kh. Kuzikyants; G. V. Lukina; Ya. A. Sigidin; A. V. Karaulov; S. N. Bykovskaya; E. L. Nasonov (Научно-практическая ревматология)
Along with its basic activity in removing B-lymphocytes, rituximab (RTM) causes depletion of a population of CD20+ T cells that can pro- duce a variety of immunoregulatory and proinflammatory cytokines and chemokines. Objective: to define a role of multiplex cytokine analysis in the evaluation of the efficiency of using RMT in rheumatoid arthritis (RA). Subjects and methods. Thirty-four patients with the valid diagnosis of RA according to the ACR criteria of 1987 were examined. The con- centrations of cytokines were measured using the xMAP technology (27-plex). Results and discussion. In the group of patients with a clinical response to therapy with the gene engineering biological agent, there was a decrease in the concentrations of interleukins (IL) 1β, 1ra, 2, 4, 6, 9, and 13, granulocyte macrophage colony-stimulating factor (GM- CSF), γ-interferon (IFN-γ), monocyte chemoattractant 1 at week 8 of therapy; that in IL 1β, 1ra, 2, 5, 6, 9, 10, 12, 13, and 15, fibroblast growth factor 2 (FGF-2), GM-CSF, IFN-γ, and tumor necrosis factor-α at week 24, and that in IL-9 at week 40. The no-clinical response group showed a reduction in GM-CSF at week 8 and in IL-2 and macrophage inflammatory protein 1β (MIP-1β) at week 40, and an increase in IL-8 at week 8. At week 8 after drug infusion, the elevated levels of IL-17 and MIP-1β can be identified as possible early pre- dictors of a response (at week 40). Comparison of the baseline cytokine levels in the groups with different clinical response demonstrated a more than three-fold increase in the concentrations of IL 4, 5, 7, 8, 10, 12, 13, 15, 17, IFN-γ, and vascular endothelial growth factor, and IL-8 at weeks 8 and 40, respectively.